A New Variable-Coefficient Riccati Subequation Method for Solving Nonlinear Lattice Equations. (20th March 2013) - Meng, Fanwei
Abstract : We propose a new variable-coefficient Riccati subequation method to establish new exact solutions for nonlinear differential-difference equations. For illustrating the validity of this method, we apply it to the discrete (2 + 1)-dimensional Toda lattice equation. As a result, some new and generalized traveling wave solutions including hyperbolic function solutions, trigonometric function solutions, and rational function solutions are obtained.